Outsourcing of Business Registration Activities : Lessons from Experience - International Finance Corporation; Multilateral Investment Guarantee Agency; World Bank (Washington, DC, 2017)
In the private sector, outsourcing has become a recognized feature of the business scene. While there are various reasons for contracting out functions to external organizations, in general the justification relates to the potential cost-benefit from adopting this approach. This study set out to ascertain whether the same considerations applied to administrative procedures associated with starting a business. Did business registries outsource any or all of their functions? If so, did the same considerations apply as for the private sector? Were there lessons to be learned from their experience? Responses to these and other questions were received from 53 registries. This paper is not about global commerce, at least, not in the usual sense. It is about some of the more mundane administrative procedures that underpin the activities of the private sector, the basics that help it to function. Business registration is seen as a key factor in determining the investment climate of a country.